Risk factors, family psychopathology and long-term outcomes of selective mutism - Koskela, Miina (fi=Turun yliopisto|en=University of Turku|, 2024)
Selective mutism (SM) is an anxiety disorder that usually onsets during childhood. Its main symptom is inability to speak in some situations despite normal speech in others. Sociodemographic factors are known risk factors for psychiatric disorders, but research on their association with SM is limited. Psychiatric disorders tend to cluster in families, but findings on psychiatric disorders among family members of subjects with SM are not uniform. The aim of the current thesis was to validate the use of the SM diagnosis and to investigate family psychopathology and demographic risk factors associated with SM, along with its long-term outcomes. The study used a nested register-based case-control setting. Information on subjects, controls and their parents and siblings were obtained from Finnish health registers. Each subject was matched by gender and age with four control subjects. Study I included 860 subjects with SM along with 3,250 controls, and Study II included 658 subjects with 1,661 siblings and 2,029 controls with 4,120 siblings. The validity of the SM diagnosis in use was evaluated by assessing the patient records of a subsample of 53 subjects in Study I. Study I examined parental psychopathology, parental age, maternal socioeconomic status, urbanicity, maternal marital status and parental immigration status. Study II explored sibling psychopathology. A systematic literature review was conducted to investigate the long-term psychiatric outcomes of SM. The studies found that both parental and sibling psychopathology were associated with SM among the subjects and showed non-specific pattern of clustering of disorders. The validity of SM diagnosis was found to be good. Advanced paternal age, low maternal socioeconomic status and single motherhood at the time of the child’s birth were also associated with SM. Among studies included in the review, most children with SM recovered during the follow-up period, but anxiety disorders were common later in life. Current findings point towards a shared etiology between SM and other psychiatric and neurodevelopmental disorders. In particular, the relationship between the etiology of SM and autism spectrum disorders requires further study. High-quality studies with follow-up times extending to adulthood are warranted.

Valikoivan puhumattomuuden riskitekijät sekä pitkäaikaisvaikutukset Valikoiva puhumattomuus (VP) on ahdistuneisuushäiriö, jonka pääasiallinen oire on puhumattomuus tietyssä tilanteessa. Erilaiset väestötieteelliset tekijät on todettu riskitekijöiksi psykiatrisille häiriöille, mutta näitä on tutkittu VP:en suhteen vähäisesti. Psykiatriset häiriöt kasautuvat perheisiin, mutta aiemmat löydökset VP:sta ja perheessä todetuista psykiatrisista häiriöistä eivät ole yhdenmukaisia. Väitöskirjan tavoitteena on arvioida VP diagnoosien luotettavuutta ja tutkia perheen psykiatristen häiriöiden ja väestötieteellisten riskitekijöiden yhteyttä VP:een sekä VP:n psykiatrisia pitkäaikaisvaikutuksia. Tutkimuksessa käytettiin pesitettyä tapauskontrolli asetelmaa ja tiedot tapauksista sekä kontrolleista kerättiin suomalaisista rekistereistä. Yhtä tapausta kohden kerättiin neljä iän ja sukupuolen suhteen kaltaistettua kontrollia. Ensimmäisessä tutkimuksessa oli mukana 860 tapausta sekä 3250 kontrollia, ja toisessa 658 tapausta sekä heidän 1661 sisarustaan ja 2029 kontrollia sekä heidän 4120 sisarustaan. VP diagnoosien luotettavuus arvioitiin käymällä läpi 53 tapauksen potilasasiakirjat. Tutkimuksissa selvitettiin vanhempien ja sisarusten psykiatristen häiriöiden, vanhempien iän, äidin sosioekonomisen aseman, äidin parisuhteen, kaupungissa asumisen sekä maahanmuuton yhteyttä VP:een. VP:en pitkäaikaisvaikutuksia selvitettiin toteuttamalla systemaattinen kirjallisuuskatsaus. Tutkimuksissa todettiin, että sekä vanhempien että sisarusten psykiatriset häiriöt ovat yhteydessä VP:een, ja yhteys koski laajasti erityyppisiä psykiatrisia häiriöitä. VP diagnoosien luotettavuus arvioitiin hyväksi. Isän korkea ikä, äidin matala sosioekonominen asema sekä se, ettei äiti ollut parisuhteessa lapsen syntyessä olivat yhteydessä VP:een. Systemaattisen kirjallisuuskatsauksen sisältämissä tutkimuk-sissa lähes kaikkien tapausten oireet väistyivät seurannan aikana, mutta ahdistu-neisuushäiriöt ovat yleisiä myöhemmin elämässä. Tulokset viittaavat yhteiseen etiologiaan VP:en sekä muiden psykiatristen ja kehityksellisten häiriöiden välillä. Erityisesti VP:n yhteyttä autismikirjon häiriöihin tulisi tutkia jatkossa. Laadukkaiden, aikuisuuteen jatkuvien, seurantatutkimusten tarve on ilmeinen.